Extracellular cyclophilin a augments platelet-dependent thrombosis and thromboinflammation - Von Ungern-Sternberg, Saskia N. I.; Vogel, Sebastian; Walker-Allgaier, Britta; Geue, Sascha; Maurer, Andreas; Wild, Anna-Maria; Muenzer, Patrick; Chatterjee, Madhumita; Heinzmann, David; Kremmer, Elisabeth; Borst, Oliver; Loughran, Patricia; et al. (Thrombosis and Haemostasis, 2017)
Cyclophilin A (CyPA) is involved in the pathophysiology of several inflammatory and cardiovascular diseases. To our knowledge, there is no specific inhibitor targeting extracellular CyPA without affecting other extracellular cyclophilins or intracellular CyPA functions. In this study, we developed an antibody-based inhibitor of extracellular CyPA and analysed its effects in vitro and in vivo. To generate a specific antibody,mice and rats were immunized with a peptide containing the extracellular matrix metalloproteinase inducer binding site and various antibody clones were selected and purified. At first, antibodies were tested for their binding capacity to recombinant CyPA and their functional activity. The clone 8H7-mAb was chosen for further experiments. 8H7-mAb reduced the CyPA-induced migration of inflammatory cells in vitro and in vivo. Furthermore, 8H7-mAb revealed strong antithrombotic effects by inhibiting CyPAdependent activation of platelets and thrombus formation in vitro and in vivo. Surprisingly, 8H7-mAb did not influence in vivo tail bleeding time or in vitro whole blood coagulation parameters. Our study provides first evidence that antibody-based inhibition of extracellular CyPA inhibits thrombosis and thromboinflammation without affecting blood homeostasis. Thus, 8H7-mAb may be a promising compound for thrombi modulation in inflammatory diseases to prevent organ dysfunction.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Cyclophilin A; Inflammation; Platelets; Thrombosis